Considerations on the Oral Cancer Screening Program from a Scientific, Technological, and Social Perspective - Diosky Ferrer Vilches; Ana Belkys Hernández Millan; Dayamí Medina Quintero; Onelio García González; Regla Martínez de la Cotera (Medisur)
Oral cancer rates have been increasing. There are several ongoing studies on this subject that specifically focus on the risk factors for this type of cancer. Addressing this problem holistically will allow analyzing this phenomenon using various approaches. For such reasons, we conducted a review of research papers published in electronic journals in SciELO and PubMed databases in order to demonstrate the contribution of the Oral Cancer Screening Program to Cuban public health and its interrelation with science, technology, and society. The assumed starting point allows stating that the science, technology and society approach is not only a field of study concerned with the complex interrelationships between science, technology, and the societies in which they develop. In addition, this approach is related to all social areas. Therefore, it is not just a matter of thought or study; it is, above all, a practical-existential problem.